A new species of the genus Microhyla (Amphibia: Anura: Microhylidae) from Guizhou Province, China - Li, Shize; Zhang, Meihua; Xu, Ning; Lv, Jingcai; Jiang, Jianping; Liu, Jing; Wei, Gang; Wang, Bin (Zootaxa, 2019)
A new species of the microhylid frog genus Microhyla is described from the Fanjing Mountain of Guizhou Province, China. Phylogenetic analyses based on DNA sequences of the the mitochondrial 12S rRNA, 16S rRNA and COI genes supported the new species as an independent lineage, closely related to M. beilunensis, M. mixtura and M. okinavensis. The uncorrected genetic distance on 16S rRNA gene between the new species and its closest congeners M. beilunensis, M. mixtura and M. okinavensis are 3.5%, 4.6% and 4.6% respectively. The new species is distinguished from its congeners by a combination of the following morphological characters: (1) body of medium size (SVL 19.0–22.7 mm in males and 22.5–23.0 mm in females); (2) disk and dorsal median longitudinal groove on finger tips absent; (3) toe with rudimentary webbing at base; (4) disk with dorsal median longitudinal groove present at toe tips except for the toe I; (5) two metatarsal tubercles on palm; (6) tibiotarsal articulation reaching the level between eye to nostril when leg stretched forward; (7) a distinct V-shaped white stripe on the upper midsection. The new species is known only from the type locality, and thus the finding of it has contributed to the endemic species diversity of China. It is needed to take strategy to protect the species and habitats due to the increased threats of environmental changes.